2019
DOI: 10.1103/physrevlett.122.170501
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Controlled Quantum Teleportation for Discrete Variables on Linear Optical Devices

Abstract: We report an experimental implementation of tripartite controlled quantum teleportation on the quantum optical devices. The protocol is performed through bi-and tripartite entangled channels of discrete variables and qubits encoded in polarization of individual photons. The experimental results demonstrate successful controlled quantum teleportation with a fidelity around 83%, well above the classical limit. By realizing the controlled quantum teleportation through biseparable state, we show that tripartite en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 49 publications
0
29
0
Order By: Relevance
“…Another group of possible applications of the entangled states is related to the proposals of quantum internet [21]. In particular, quite recently, the experiment which can lead to the construction of quantum routers was performed and presented in [22]. At this point, one should mention the successful quantum teleportation from the surface of the Earth to the satellite [23], which opens new perspectives in the development of quantum technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Another group of possible applications of the entangled states is related to the proposals of quantum internet [21]. In particular, quite recently, the experiment which can lead to the construction of quantum routers was performed and presented in [22]. At this point, one should mention the successful quantum teleportation from the surface of the Earth to the satellite [23], which opens new perspectives in the development of quantum technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum teleportation is at the core of quantum information technologies [1][2][3][4]. Ever since the seminal work by Bennett et al [5], teleportation has been demonstrated in various physical platforms [6][7][8][9][10][11][12][13][14][15] and many different protocols have been proposed to date [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Recently, developments have been directed to its potential applications for long-distance quantum communications [31][32][33][34][35], inter-chip communications [36] and other versatile functionalities toward scalable quantum architectures [37][38][39].…”
mentioning
confidence: 99%
“…In this respect, applying a unitary operation at the receiver's station may not always be optimal in practice. However, existing teleportation protocols to date conventionally limit Bob's operation to unitary [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], which would also significantly limit the fault-tolerance of quantum teleportation.…”
mentioning
confidence: 99%
See 2 more Smart Citations